2012
DOI: 10.1038/nrm3267
|View full text |Cite|
|
Sign up to set email alerts
|

Illuminating the functional and structural repertoire of human TBC/RABGAPs

Abstract: The Tre2-Bub2-Cdc16 (TBC) domain-containing RAB-specific GTPase-activating proteins (TBC/RABGAPs) are characterized by the presence of highly conserved TBC domains and act as negative regulators of RABs. The importance of TBC/RABGAPs in the regulation of specific intracellular trafficking routes is now emerging, as is their role in different diseases. Importantly, TBC/RABGAPs act as key regulatory nodes, integrating signalling between RABs and other small GTPases and ensuring the appropriate retrieval, transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
121
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 76 publications
2
121
0
1
Order By: Relevance
“…TBC domains usually function as GAPs for members of the Rab family of small G-proteins using a dual-finger mechanism (30,31). Although the TBC1D7 TBC domain (residues 50 -231) does not contain the two most critical catalytic ("finger") residues (25, 31), TBC1D7 was shown to specifically inac-* This work was supported by CAS Grant XDB08010303, and the Department of Defense Grant W81XWH-13-1-0059 (TS120073) (to W.…”
Section: Tuberous Sclerosis Complex (Tsc)mentioning
confidence: 99%
“…TBC domains usually function as GAPs for members of the Rab family of small G-proteins using a dual-finger mechanism (30,31). Although the TBC1D7 TBC domain (residues 50 -231) does not contain the two most critical catalytic ("finger") residues (25, 31), TBC1D7 was shown to specifically inac-* This work was supported by CAS Grant XDB08010303, and the Department of Defense Grant W81XWH-13-1-0059 (TS120073) (to W.…”
Section: Tuberous Sclerosis Complex (Tsc)mentioning
confidence: 99%
“…In addition, the active site of many small GTPases is completed by a catalytic "arginine finger" that is used, e.g., by Ras-, Rho-, and RabGAPs, but is not needed for catalysis in Ran and Rap. Conventional TBC domains possess conserved arginine and glutamine residues (2,11). In the case of activation of Rab33 (mouse) by the yeast GAP Gyp1, it was shown that a glutamine residue of Gyp1 (termed trans-glutamine) positions the water molecule rather than the conserved glutamine in Rab33 (termed cis-glutamine) (11).…”
mentioning
confidence: 99%
“…Interaction with effectors takes place in the GTPbound "on" state, and the inactivation occurs via GTP hydrolysis to GDP; this is catalyzed by GTPase activating proteins (GAPs), thereby downregulating the GTPase. Most RabGAPs contain Tre2-Bub2-Cdc16 (TBC) domains, and accelerate the intrinsic GTP hydrolysis rate up to 10 5 -fold (2,3). As regulators of Rabdependent pathways, RabGAPs are involved in a number of diseases, contributing to viral and bacterial infection, cancer development, predisposition to obesity, and others (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The conserved arginine and glutamine finger structures in the TBC domain were shown to be required for the GAP activity of the TBC domain-containing proteins, and the mutations of the two amino acids can abolish the GAP activity (28,47,48). We examined the effects of the corresponding mutant forms of EPI64B that bear the two respective point mutations.…”
Section: Discussionmentioning
confidence: 99%